The role of the nursing workforce in health system resilience during disasters: a scoping review of empirical studies - Katherine Kruger; Petra Brysiewicz; Jody Lori; Sue Anne Bell (International Journal of Nursing Studies Advances)
Aim: The aim of this study was to explore the extent to which the nursing workforce contributes to health system resilience globally through a scoping review of peerreviewed literature. Introduction: The World Health Organization (WHO) has emphasized the need for the development of resilient health systems to meet current and future disaster readiness needs. The WHO has also emphasized mechanisms that will achieve this goal including a focus on strengthening the global nursing workforce to achieve the Sustainable Development Goals. However, there is limited synthesized research focusing on the contributions of the nursing workforce in developing and fostering health system resilience globally. Methods: Using Joanna Briggs Institute methodology for scoping reviews, three key databases (PubMed, CINAHL, and Scopus) were searched for publications from 2006 until April 2024. English-language, research studies, and quality or process improvement projects were included. Systematic and scoping reviews, as well as studies focused on individual resilience, were excluded. Studies meeting search criteria were exported and screened first by title and abstract and subsequently underwent a full-text review using Covidence software. Quantitative and qualitative data from studies meeting inclusion criteria were extracted and analyzed according to study objectives to create a narrative synthesis. This study was registered in Open Science Framework on May 28, 2024. Results: Eleven articles were included of the 795 total retrieved. Overall, there is limited discussion of the nursing workforce in health system resilience. Eight of the 11 articles (73 %) suggest that the nursing workforce is involved in operationalizing resilience during disasters, 10 articles (91 %) call for nurses to be leaders in policy and the development of resilient health systems, however, this review found zero reports in the literature of the nursing workforce’s role in the planning, development, and leadership of resilient systems. Implications: Nurses are essential to resilient health systems, however, there is limited research examining the nursing workforce and its contributions to resilient health systems, particularly within disaster contexts. More targeted research on nursing workforce contributions to achieve resilient health systems is needed.